Protective efficacy of a Zika purified inactivated virus vaccine candidate during pregnancy in marmosets - In-Jeong Kim; Olga Gonzalez; Michael P. Tighe; Paula A. Lanthier; Madeline J. Clark; Kelsey L. Travis; Timothy C. Low-Beer; Kathleen G. Lanzer; Derek T. Bernacki; Frank M. Szaba; Rafael A. De La Barrera; Vincent Dussupt; et al. (npj Vaccines, 2024)
Abstract Zika virus (ZIKV) infection during pregnancy poses significant threats to maternal and fetal health, leading to intrauterine fetal demise and severe developmental malformations that constitute congenital Zika syndrome (CZS). As such, the development of a safe and effective ZIKV vaccine is a critical public health priority. However, the safety and efficacy of such a vaccine during pregnancy remain uncertain. Historically, the conduct of clinical trials in pregnant women has been challenging. Therefore, clinically relevant animal pregnancy models are in high demand for testing vaccine efficacy. We previously reported that a marmoset pregnancy model of ZIKV infection consistently demonstrated vertical transmission from mother to fetus during pregnancy. Using this marmoset model, we also showed that vertical transmission could be prevented by pre-pregnancy vaccination with Zika purified inactivated virus (ZPIV) vaccine. Here, we further examined the efficacy of ZPIV vaccination during pregnancy. Vaccination during pregnancy elicited virus neutralizing antibody responses that were comparable to those elicited by pre-pregnancy vaccination. Vaccination also reduced placental pathology, viral burden and vertical transmission of ZIKV during pregnancy, without causing adverse effects. These results provide key insights into the safety and efficacy of ZPIV vaccination during pregnancy and demonstrate positive effects of vaccination on the reduction of ZIKV infection, an important advance in preparedness for future ZIKV outbreaks.